Teacher Trainees' Experiences of the Components of ICT Competencies and Key Factors in ICT Competence Development in Work-Based Vocational Teacher Training in Finland - Jiri Vilppola; Joni Lämsä; Katja Vähäsantanen; Raija Hämäläinen (European Research Network Vocational Education and Training (VETNET), 2022)
Context: This research was conducted in the context of Finnish vocational education and training (VET) teacher training. The teacher training was work-based, meaning that each teacher trainee was already working as an unqualified VET teacher. Workplaces were comprehensively utilised as the learning environment, with teacher training support also being provided in the form of contact days, webinars, and online learning activities.  Approach: We aimed to explore the main components of information and communications technology (ICT) competencies among vocational teacher trainees within work-based training and also to reveal the supportive and challenging factors related to developing ICT competencies within the training. Overall, 44 vocational teacher trainees participated in our study. The data were analysed via qualitative content analysis.  Findings: Six main ICT competence components were identified during the work-based training: (1) The use and creation of digital learning materials, (2) the planning and use of digital learning environments, (3) synchronous digitally enhanced teaching, (4) general ICT competencies, (5) digital interaction, and (6) digital assessment. The development of teachers' ICT competencies was supported by their own active use of ICT and by experimenting with the ICT software and ideas presented by the teacher training staff. Challenging factors in ICT development included the continuous feeling of haste and the lack of time in the workplace, as well as the failure to recognise prior ICT competencies within the teacher training. This could limit the development of ICT competencies. Conclusions: Work-based VET teacher training has the potential to develop teacher trainees' ICT competencies because it allows immediate implementation and experimentation with regard to new ICT ideas and tools. By aligning this research with prior research, it is possible to construct a comprehensive ICT competence framework to support VET teacher training and workplace development.